Resting Heart Rate Variability: Exploring Associations with Symptom Severity in Adults with Substance Use Disorders and Posttraumatic Stress - D’Souza, Johann M. (J Dual Diagn, 2018)
OBJECTIVE: Substance use disorders (SUDs) and post-traumatic stress symptoms are commonly comorbid. Previous studies have established that those with SUD or post-traumatic stress disorder (PTSD) have lower high frequency-heart rate variability (HF-HRV) compared to controls, suggesting low HF-HRV may be a biomarker of a common physiological mechanism underlying both disorders. We evaluated HF-HRV as a potential biomarker of a common underlying process by testing whether lower HF-HRV related to greater severity of substance use and PTSD symptoms in individuals with both substance use disorders and at least four symptoms of PTSD. METHODS: HF-HRV was measured in 49 adults with SUD and at least four symptoms of PTSD. We performed a series of regressions controlling for age to test whether low HF-HRV was associated with greater SUD and PTSD symptom severity. SUD symptoms were measured by the Addiction Severity Index and PTSD symptoms were measured by the Clinician-Administered PTSD Scale and the PTSD Checklist. RESULTS: After controlling for age, low resting HF-HRV was significantly associated with drug and alcohol symptom severity but not PTSD symptom severity. CONCLUSIONS: HF-HRV may be more sensitive to the severity of drug and alcohol use rather than PTSD. Findings may suggest that in PTSD populations, HF-HRV may primarily index comorbid SUD symptoms. HF-HRV could serve as an objective measure of substance use severity and should be further investigated as a predictor of outcomes in treatment for SUD.